Pemeranan Tokoh Rangda Dalam Naskah Rangda Ing Jirah Karya Jeannete Lauren Adaptasi Novel Janda Dari Jirah Karya Cok Sawitri - Surya Chintya Dharma; Wahid Nurcahyono; Catur Wibono (Institut Seni Indonesia Yogyakarta, 2023)
Tokoh Rangda Ing Jirah dalam naskah Rangda Ing Jirah – The Legend Of Calonarang karya Jeannete Lauren menjadi salah satu daya tarik untuk diwujudkan kedalam bentuk tokoh tiga dimensi diatas panggung karena peran yang dimainkan dalam satu karakter tokoh mengalami perkembangan dari tokoh sebagai Rangda Ing Jirah serta kemudian menjadi manifestasi Durga, di mana hal tersebut menggambarkan persona dan shadow seperti yang disampaikan Carl Jung. Pemilihan karakter tokoh Rangda sebagai karya tugas akhir keaktoran dilatar belakangi oleh sudut pandang tentang kisah Calonarang, kali ini tokoh Rangda Ing Jirah ialah tokoh protagonis. Adapun teori pemeranan dalam penciptaan tokoh Rangda Ing Jirah yang digunakkan ialah teori pemeranan representasi menurut Uta Hagen. Dalam merepresentasikannya didukung pula oleh teknik substitusi di mana menempatkan diri aktor dalam kenyataan kehidupan sendiri tanpa menggunakan kata seakan-akan. Pementasan tokoh ini bertajuk dramatari. Selain dialog tokoh, pemeranan akan didukung dengan tembang geguritan serta tarian Bali.Rangda Character Acting in Jeannete Lauren's Play “Rangda Ing Jirah”, Adaptation Of Cok Savitri’s Novel “Janda dari Jirah”The figure of Rangda Ing Jirah in the script Rangda Ing Jirah – The Legend Of Calonarang by Jeannete Lauren is one of the attractions to be embodied in the form of a three-dimensional character on stage because the role played in one character develops from a character as Rangda Ing Jirah and then becomes the manifestation of Durga, where it describes the persona and shadow as conveyed by Carl Jung. The background of the selection of the character Rangda as his final acting work is the perspective of the Calonarang story, this time the character Rangda Ing Jirah is the protagonist. The role theory used in the creation of the character Rangda Ing Jirah is the theory of representational play according to Uta Hagen. In representing it, it is also supported by substitution techniques in which the actor places himself in the reality of his own life without using the word “as if”. The performance of this character is entitled “dramatari”. In addition to character dialogue, the performance will be supported by “geguritan” songs and Balinese dances.